Molecular mechanisms of human hemoglobin switching: selective undermethylation and expression of globin genes in embryonic, fetal, and adult erythroblasts. - Mavilio, F (1983)
The globin chain synthetic pattern and the extent of DNA methylation within embryonic, fetal, and adult beta-like globin gene domains were evaluated in greater than or equal to 90% purified human erythroblasts from yolk sacs and fetal livers in the 6- to 12-wk gestational period as well as from adult marrows. The 6-wk erythroblasts produce essentially embryonic epsilon chains, whereas the 12-wk erythroblasts synthesize largely fetal gamma globin and the adult marrow erythroblasts synthesize almost exclusively adult beta chains. In all phases of ontogenic development, a strong correlation exists between DNA hypomethylation in the close flanking sequences of globin genes and their expression. These results suggest that modulation of the methylation pattern may represent a key mechanism for regulating expression of human globin genes during embryonic leads to fetal and fetal leads to adult Hb switches in humans. In ontogenic development this mechanism might in turn correlate with a gradual modification of chromatin structure in the non-alpha gene cluster, thus leading to a 5' leads to 3' activation of globin genes in a balanced fashion.